Enantioselective transesterification of a propargyl tertiary alcohol by Candida antarctica lipase A: A reaction medium engineering approach - Laerte Ganeo Neto; Cintia Duarte Freitas Milagre; Humberto Márcio Santos Milagre (Results in Chemistry, 2023)
Lipase A from Candida antarctica (CAL-A) is widely known to accept bulky substrates, such as tertiary alcohols. These compounds are important building blocks in organic synthesis processes, and they are found in many natural products. Under an organic medium and in the presence of an acyl donor, CAL-A can act as a chiral catalyst in the kinetic resolution (KR) of these substrates via an enantioselective transesterification reaction. Herein, we report a new protocol developed for the KR of the propargyl tertiary alcohol 2-phenyl-3-butyn-2-ol ((rac)-1) catalyzed by CAL-A. A reaction medium engineering study was performed by varying the following conditions involved in the system: temperature, solvent, acyl donor, acyl donor concentration, and enzyme loading. After optimization, we developed a more efficient system with a lower enzyme/substrate ratio using a commercially available and immobilized wild-type CAL-A.